The effect of Comic Strips and Learning Motivation toward the Studentsâ Achievement in English Writing in Eighth Grade of SMPN 2 Sawan. - ., KADEK DEVY MARLENI; ., Dra. Luh Putu Artini, MA., Ph.D.; ., Drs. I Wayan Suarnajaya,MA., Ph.D. (Jurnal Pendidikan Bahasa Inggris, 2013)
This thesis aimed at investigating whether the implementation of Comic Strips technique and the studentsâ learning motivation gave a significant effect to the students âwriting achievement. The study was an experimental study by applying 2x2 factorial designs. The population was 4 classes (120 students) of grade VIII in SMPN 2 Sawan in the academic year 2012/2013, in which 2 classes were samples which were assigned into two groups, i.e. experimental group and control group. The research data were collected through tests that were analyzed by using Statistical Two-Way Anova and Tukey Test. The result shows that, first, there was a significant different on the studentsâ writing achievement between the students who were taught by using Comic Strip Technique and Conventional Technique. Second, there was significant difference in writing skill between the students having a high learning motivation taught by using Comic Strip and those taught by using Conventional Learning, third, there was significant difference in writing skill between the students having a low learning motivation taught by using comic strip and those taught by using Conventional Learning, and there is no interactional effect of teaching media and learning motivation level upon studentsâ writing skill. keyword : Comic Strips technique, learning motivation, writing.